Lenalidomide enhances antigen-specific activity and decreases CD45RA expression of T cells from patients with multiple myeloma - Neuber, Brigitte; Krämer, Isabelle; Tolliver, Claudia; Schönland, Stefan; Hegenbart, Ute; Hose, Dirk; Witzens-Harig, Mathias; Ho, Anthony Dick; Goldschmidt, Hartmut; Klein, Bernard; Hundemer, Michael (The journal of immunology, 2011)
The aim of this study was to investigate whether the specific T cell response against the multiple myeloma Ag HM1.24 is enhanced by the immunomodulatory drug lenalidomide (Revlimid). Ag-specific CD3+CD8+ T cells against the HM1.24 Ag were expanded in vitro by dendritic cells in 29 healthy donors and 26 patients with plasma cell dyscrasias. Ag-specific activation was analyzed by IFN-γ, granzyme B, and perforin secretion using ELISA, ELISPOT assay, and intracellular staining, and generation of Ag-specific T cells was analyzed by tetramer staining. Expression of T cell maturation markers (CD45RA, CD45R0, CCR7, and CD28) was investigated by flow cytometry. We found that activation of HM1.24-specific T cells from healthy donors and patients with plasma cell dyscrasias was enhanced significantly by lenalidomide and furthermore that the impact of lenalidomide on T cells depends on the duration of the exposure. Notably, lenalidomide supports the downregulation of CD45RA on T cells upon activation, observed in healthy donors and in patients in vitro and also in patients during lenalidomide therapy in vivo. We showed for the first time, to our knowledge, that lenalidomide enhances the Ag-specific activation of T cells and the subsequent downregulation of CD45RA expression of T cells in vitro and in vivo.
Gesehen am 21.09.2022